Improving the Ability to Read Drama Texts with the Discovery Learning Model in Students - Jumriati, Jumriati; Efendi, Anwar (UNIVERSITAS PAKUAN, 2025)
This study aims to determine the ability to read drama texts through the application of the discovery learning learning model in grade XI students of SMK Negeri 1 Sebatik Barat. This research is a class action research (PTK) that has been carried out at SMK Negeri 1 West Sebatik. The subjects in this class action research are students of class XI AKL A at SMK Negeri 1 Sebatik Barat, consisting of 20 female students and 11 male students. The object of this study is the ability to read drama texts through the application of the discovery learning learning model. The research was carried out in two cycles consisting of four stages each cycle, namely planning, action implementation, observation, and reflection. The data collection techniques used in this study include, observation, field notes, tests, and documentation. The results of the study show that the application of the discovery learning learning model can improve the ability to read drama texts in grade XI students of SMK Negeri 1 West Sebatik. The improvement is shown from the quality of the learning process which is reflected in students' attention to learning, students' enthusiasm for learning, students' activeness, and students' timeliness in collecting assignments. The increase in product can be seen from the average score of reading drama texts from pre-action to cycle II. In the pre-action, an average score of 42.54% was obtained, then in the first cycle it increased to 63.10% and in the second cycle it increased significantly by 85.69%. It can be concluded that the application of the discovery learning learning model can improve the quality of the learning process and improve the learning outcomes of students in class XI of SMK Negeri 1 West Sebatik.